Modelling co-combustion of bituminous coal and pine sawdust: Thermal behaviour - Garikai T. Marangwanda (Elsevier, 2021)
This study focused on the effects of introducing pine sawdust and bituminous coal in a down fired combustion reactor. Co-combustion of coal and biomass waste provides an alternative to biomass waste management as well as efficiency improvement with regards to boiler optimisation if correctly applied. A Computational Fluid Dynamics model, using ANSYS Fluent, was employed alongside experimental data to study the behaviour of this co-combustion process. The co-combustion model employed was based on the discrete phase submodel which tracks discrete solid fuel particles in a fluid continuum comprising of the gaseous oxidant, intermediate species, and products. The other important submodels used in this study comprised of the single kinetic devolatilisation submodel and the multiple surface heterogenous char reaction submodel. Two homogenous volatile combustion mechanisms were tested which were the refined Westbrook and Dryer 2-step reaction mechanism as well as the refined Jones and Lindstedt 4-step reaction mechanism. The effect of particle size was monitored in detail by employing a shape factor of 0.87 for biomass particles towards the drag law and the radiative heat transfer tested the effect of using the Discrete Ordinate and P1 radiation submodels. The results showed an increase in burnout for 0.2 s residence time from 37% to 72% when sawdust was introduced in the combustion chamber whilst the temperature profiles showed a general decrease in maximum temperatures attainable as the sawdust proportion increased.